Development of microsatellite loci for the riparian tree species Melaleuca argentea (Myrtaceae) using 454 sequencing. - Nevill, Paul; Williams, A.; Krauss, S.; Bradbury, D.; Samaraweera, S.; Gardner, M. (2013)
UNLABELLED: • PREMISE OF THE STUDY: Microsatellite primers were developed for Melaleuca argentea (Myrtaceae) to evaluate genetic diversity and population genetic structure of this broadly distributed northern Australian riparian tree species. • METHODS AND RESULTS: 454 GS-FLX shotgun sequencing was used to obtain 5860 sequences containing putative microsatellite motifs. Two multiplex PCRs were optimized to genotype 11 polymorphic microsatellite loci. These loci were screened for variation in individuals from two populations in the Pilbara region, northwestern Western Australia. Overall, observed heterozygosities ranged from 0.27 to 0.86 (mean: 0.52) and the number of alleles per locus ranged from two to 13 (average: 4.3). • CONCLUSIONS: These microsatellite loci will be useful in future studies of the evolutionary history and population and spatial genetic structure in M. argentea, and inform the development of seed sourcing strategies for the species.